AN EXPERIMENTAL STUDY OF VRIKSHAYURVEDA SEED TREATMENTS ON GERMINATION RATE AND ACTIVE INGREDIENT OF BAKUCHI (PSORALEA CORYLIFOLIA LINN.) BY HPLC METHOD - *Gangadhar T. Aralelimath; Shraddha U. Nayak; Gireesh M. Ankad; Harsha V. Hegde; S S Shirurmath (International Journal of Ayurveda and Pharma Research, 2019)
Bakuchi (Psoralea corylifolia Linn.) is one of the important endangered medicinal plants used in Ayurveda and other Traditional systems. Its cultivation and propagation is difficult due to its low germination rate (5-7%) & prolonged seed dormancy. Bakuchi seeds made into 5 groups, the experiment was conducted in a complete randomized block design with 5 treatments and 5 replications totally 500 seeds in each group) & observed for 50 days. Control Group 1 no- seed treatment, Group 2- Standard treated with 1% conc H2SO4, Group 3 Vrikshayurvedic treatment done by soaking in milk subsequently fumigation of Vidanga & Ghee, Group 4- treated with paste of Brihati, Tila, Kamalanaala, Ghee & Group 5 treated by soaking in milk subsequently Cow dung, Vidanga & Honey applied. Number of seeds germinated, germination percentage, emergence index and relative seed germination parameters were observed. HPLC studies carried out of post harvested Bakuchi seeds of all 5 groups to know the effect of seed treatments on Psoralen content quantitatively. Overall results indicates that Group 4 (8.000 ± 0.8367) seeds soaked in 12 hrs milk followed by application of Brihati, Tila, Kamalanaala & Ghee paste for 12 hrs treatment is statistically significant (P value>0.05) in comparison with group 2 (4.600 ± 0.6782) Sulphuric acid treatment and Group 3 (4.200± 0.9165) fumigation with Honey & Vidanga. Rest of the groups shown insignificant changes on germination parameters. HPLC Results found that generally seed treatments may reduce the content of Psoralen as in control (Group 1) maximum percentage (0.04%w/w) of Psoralen is noticed. Among treatment groups Group 4 contains maximum (0.027%w/w) Psoralen next to control (0.039%w/w). Psoralen content is very less in standard Group 2 (0.022%w/w), Group 3 (0.023%w/w) & Group 4 (0.024%w/w). Maximum germination percentage was observed in Group 4 in comparison with the Group 2conventional method of treating with sulphuric acid. Estimation of Psoralen contents in the seeds from the plants grown by various treated seeds reveled that Group 4 is qualitatively better than standard, but inferior to the control, standard & other Vrikshayurveda seed treatment techniques used in the current experiment.